The "purification" and modeling of multi-agent monitoring system for industrial textiles. (July 2013) - Shao, Jingfeng; Wang, Jinfu; Liu, Sheng
To improve the quality of industrial textile products and ensure the accuracy of the real-time collected textile production data, we first proposed a new data fitting method, which uses the integral and differential quotient operator to obtain the basic spline function and B -spline curve by operator deduction, and then used high-order approximation method for differential operator to get the precise spline fitting function. Second, a multi-agent network-monitoring system model was built, and its work principle, main function, collaborative process, and scheduling algorithm were introduced. The application results show that the proposed data fitting method is optimum and the results are accurate. Furthermore, the system structure model based on multi-agent meets the requirements of quality control of industrial textiles.